2010
DOI: 10.3109/01421590903480113
|View full text |Cite
|
Sign up to set email alerts
|

Health economics education in undergraduate medical degrees: an assessment of curricula content and student knowledge

Abstract: The teaching and learning environment and level of student knowledge of health economics was found to differ considerably across medical schools. The delivery of health economics teaching by specialised health economists would appear to be one possible strategy to improve student knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…However, this is not to say that teaching economic analysis ought to be less rigorous. On the contrary, it has been shown that medical schools with the most intensive health economics curricula perform marginally better and those students with Economics and clinical practice S57 health economists as instructors score higher than those taught by non-health economists (Gray & Lorgelly 2010).…”
Section: Benefits and Challenges To Health Economics Integrationmentioning
confidence: 94%
“…However, this is not to say that teaching economic analysis ought to be less rigorous. On the contrary, it has been shown that medical schools with the most intensive health economics curricula perform marginally better and those students with Economics and clinical practice S57 health economists as instructors score higher than those taught by non-health economists (Gray & Lorgelly 2010).…”
Section: Benefits and Challenges To Health Economics Integrationmentioning
confidence: 94%
“…In other countries such as the US and Germany, it has been proposed that providing high-value, cost-conscious care is to become a core competency for training doctors [6,7]. Whilst there appears to be universal agreement that health economics should form an integral part of medical undergraduate training, there remains considerable diversity across medical schools in the UK in terms of the content of the health economics education and in the way the teaching is delivered [2]. …”
Section: Introductionmentioning
confidence: 99%
“…As well as the consensus to have health economics training embedded into undergraduate medical curriculum, there is also an agreement that ideally this training should be provided by health economists [2]. However there is a shortage of health economics expertise within the UK capable of meeting all the training needs [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite this increased use and need for health economics expertise, there has not been a matching increase in scholars with health economics training (Kaambwa & Frew, ). A substantial portion of the health economics courses around the world is taught outside of traditional economics departments, often by instructors with no health economics training and sometimes by instructors with very little formal economics training at all (Gray & Lorgelly, ; Sloan & Hsieh, , pxvii). In fact, many of these courses limit the definition of “health economics” to cost‐effectiveness analysis and do not include other important content such as utility theory, risk and insurance, the role of price in equilibrating markets, production functions, or externalities (see Platt & Kwasky, , for instance).…”
mentioning
confidence: 99%